2010
DOI: 10.1055/s-0030-1249035
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 Protects Pancreatic Beta Cells from the Cytotoxic Effect of Rapamycin by Inhibiting JNK and p38 Phosphorylation

Abstract: It has been reported that the immunosuppressant rapamycin decreases the viability of pancreatic beta cells. In contrast, exendin-4, an analogue of glucagon-like peptide-1, has been found to inhibit beta cell death and to increase beta cell mass. We investigated the effects of exendin-4 on the cytotoxic effect of rapamycin in beta cells. Incubation with 10 nM rapamycin induced cell death in 12 h in murine beta cell line MIN6 cells and Wistar rat islets, but not when coincubated with 10 nM exendin-4. Rapamycin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…Reason for that is not clear; however, we cannot exclude that other ROS are behind the involvement of p38 MAPK and JNK kinases upon apoptosis. Recently, it was demonstrated that exendin-4 inhibits cytotoxic induced b-cell death via a decreased phosphorylation of both p38 MAPK and JNK, through PKA signaling pathways (Kawasaki et al 2010), which is in line with our observation.…”
Section: Discussionsupporting
confidence: 93%
“…Reason for that is not clear; however, we cannot exclude that other ROS are behind the involvement of p38 MAPK and JNK kinases upon apoptosis. Recently, it was demonstrated that exendin-4 inhibits cytotoxic induced b-cell death via a decreased phosphorylation of both p38 MAPK and JNK, through PKA signaling pathways (Kawasaki et al 2010), which is in line with our observation.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with this finding, it has been reported that rapamycin activates JNK in a human glioblastoma cell line that expresses a constitutively active mutant of the epidermal growth factor receptor [24]. Furthermore, rapamycin also increased JNK phosphorylation in MIN6 cells and Wistar rat pancreatic ilets [25]. Finally rapamycin was also shown to induce a transient activation of JNK in cells expressing wild-type p53 and a sustained activation in cells expressing mutant p53 [26].…”
Section: Discussionsupporting
confidence: 69%
“…GLP-1 receptor agonists can inhibit the proapoptotic pathways triggered by a variety of stimuli, including IL-1β, TNF-α and rapamycin, by interfering with JNK and possibly p38 MAPK activation [15,19,46]. The cAMP/PKA/CREB cascade represents a central mechanism of GLP-1 action, specifically when this relates to promotion of beta cell survival [47], even though other signalling mediators may also be implicated [48,49].…”
Section: Discussionmentioning
confidence: 99%